Therapeutic bronchoscopic interventions for malignant airway obstruction: A retrospective study from experience on 547 patients - Dalar, Levent (Medicine (Baltimore), 2016)
There is no definitive consensus about the factors affecting the choice of interventional bronchoscopy in the management of malignant airway obstruction. The present study defines the choice of the interventional bronchoscopic modality and analyzes the factors influencing survival in patients with malignant central airway obstruction. Totally, over 7 years, 802 interventional rigid bronchoscopic procedures were applied in 547 patients having malignant airway obstruction. There was a significant association between the type of stent and the site of the lesion in the present study. Patients with tracheal involvement and/or involvement of the main bronchi had the worst prognosis. The sites of the lesion and endobronchial treatment modality were independent predictors of survival in the present study. The selection of different types of airway stents can be considered on the base of site of the lesion. Survival can be estimated based on the site of the lesion and endobronchial brochoscopic modality used.